Contributions of marxist aesthetics and historical-critical pedagogy to selection of content in literature teaching - Nardy, João Pedro [UNESP]; Teixeira, Lucas André [UNESP] (Universidade Estadual de Maringa, 2024)
This article writes about the problem of how to select the scholar content for literature teaching, in the context of Portuguese language classes in elementary and high school. It questions which literary works are valid, based in which criterions, and to what purposes possible, considering, also, that the educative labor may situate itself in perspective of humanization or alienation, i. e., acting against or surrendering it self to the tendency of discrepancy between multilateralism of mankind and individual existence, as shows the analysis of reality by historical-dialectical materialism underlying the research. It is adopted the thesis of the historical-critical pedagogy about the centrality of the classics, based in its values for the knowledge of reality, but inquiring which aesthetic elements allow that certain literary works as one and then to be privileged as scholar content. The research reaches the conclusion that it is necessary that the literature teacher have an historical and critical conception of reality, to face scholar object with the formation knowledge area, i. e., the concrete knowledge of literary activity referenced in the named aesthetical theory allied to a vast repertory of literary works. It concludes that, acting for the socialization of this kind of knowledge, the educative labor in literature teaching positions itself for the overcoming of the alienation not only of the students’ consciousness, but of the teacher’s work too, while it gains means to be conceived free and handcrafted, going way beyond didactic booklets and rigid curricles curriculums that act for the separation of conception and execution of the teaching work.
Contribuições da estética marxista e da pedagogia histórico-crítica à seleção de conteúdo do ensino de literatura
Keywords: literary reading; Lukács; portuguese language teaching; realism; reflection; textbook